Constructions of alcohol consumption by non-problematised middle-aged drinkers: a qualitative systematic review - Emma Muhlack; Drew Carter; Annette Braunack-Mayer; Nicholas Morfidis; Jaklin Eliott (BMC Public Health, 2018)
Abstract Background Current research into alcohol consumption focuses predominantly on problematic drinkers and populations considered likely to engage in risky behaviours. Middle-aged drinkers are an under-researched group, despite emerging evidence that their regular drinking patterns may carry some risk. Methods We searched Scopus, Ovid Medline, and Ovid PsycInfo for peer-reviewed, English-language publications appearing prior to 31 December 2015 and relating to the construction of alcohol consumption by middle-aged non-problematised drinkers. Thirteen papers were included in our thematic analysis. Results Middle-aged non-problematised drinkers constructed their drinking practices by creating a narrative of normative drinking via discourses of gender, identity, play, and learning to drink. They also used drinking norms to construct their gender and identity. Health was not identified as a significant consideration for the population of interest when constructing alcohol consumption, except where drinking behaviours were likely to harm another. Conclusions These results suggest that public health campaigns aimed at reducing alcohol consumption may be more effective if they focus on unacceptable drinking behaviours instead of personal health outcomes.